An efficient and robust technique for particulate simulation of arbitrary convex polyhedrons with adaptable material properties. (March 2023) - Knowles, Jeffrey; Ma, Yifei; Evans, T. Matthew
Abstract: Particle collision is a common phenomenon within a granular system in geotechnical applications, such as granular dampers and rockfall mitigation barriers. This work presents a new polyhedral reinforced interior shell model (PRISM) based on the discrete element method (DEM) for simulating collisions between polyhedral particles. The surfaces of these particles are constructed from a Delaunay triangulation which operates on a set of vertices and returns the corresponding hull of simplices. The proposed model is advantageous in terms of computational efficiency because of the relatively small number of fundamental components required to build a single polyhedron. This approach permits internal stiffness properties that are independent of the surface elasticity, which enables inhomogeneous properties at the particle-scale. Furthermore, the interior stiffness can vary in a controlled anisotropic manner facilitated by a relatively small number of cylinder particles that adjoin the vertices to the centroid of the polyhedron. The proposed model is validated through a series of simulations, including a free-fall test. Outcomes from this work suggest that the proposed model could potentially improve simulation efficiency and efficacy in modeling polyhedral particles with realistic geometric and physical properties.